Label-free sub-picomolar protein detection with field-effect transistors. - Estrela, P; Paul, D; Song, Q; Stadler, L; Wang, L; Huq, E; Davis, J; Ko Ferrigno, P; Migliorato, P (2010)
Proteins mediate the bulk of biological activity and are powerfully assayed in the diagnosis of diseases. Protein detection relies largely on antibodies, which have significant technical limitations especially when immobilized on two-dimensional surfaces. Here, we report the integration of peptide aptamers with extended gate metal-oxide-semiconductor field-effect transistors (MOSFETs) to achieve label-free sub-picomolar target protein detection. Specifically, peptide aptamers that recognize highly related protein partners of the cyclin-dependent kinase (CDK) family are immobilized on the transistor gate to enable human CDK2 to be detected at 100 fM or 5 pg/mL, well within the clinically relevant range. The target specificity, ease of fabrication, and scalability of these FET arrays further demonstrate the potential application of the multiplexable field effect format to protein sensing.